ҚАРАҚАЛПАҚ, ҚЫРҒЫЗ ҲАМ ӨЗБЕК ПРОЗАСЫНДА ОБРАЗЛАР ТИПОЛОГИЯСЫ - Каниязова, Ж.О. (FAN va JAMIYAT, 2020)
The article carried oud comparative typological analysis and showed typological feature of novel «Taqdir suqmoqlari» by Karakalpak writer Sh.Seytov, «Sarvqomat dilbarim» by kirgiz writer Ch.Aitmatov and «On sakkizga kirmagan kim bor?» by Uzbek writer Sh.Kholmirzaev.